Reversible Thinking Ability in Solving Mathematics Problems - Pebrianti, Aneu; Juandi, Dadang (Mathematics Education Study Program, 2023)
Reversible thinking is the process of thinking by reversing the order of actions. Reversible thinking is an important aspect in helping to improve students' problem-solving ability. This research aims to analyze qualitative studies related to students' reversible thinking ability at elementary, middle, and high school levels in the period 2002 - 2022. The research method uses a Systematic Literature Review (SLR) that collects primary data that has been published in Sinta and Scopus indexed journals. Data extraction was adjusted to the selection criteria so that 19 articles were collected. Data analysis used a qualitative approach. Data grouping was done based on publication year, education level, demographics, journal indexer, material analyzed, and research results. The results shows that research related to reversible thinking ability became a trend in research in 2015-2022 with the topic of algebra. The studies related to this reversible thinking process are mostly conducted in the Java region at the elementary school level. However, this reversible thinking ability at all levels of education is still low. Based on the three aspects of reversible thinking, working backwards is the most difficult aspect for students to do. One of the reasons is because students do not understand the concept thoroughly. This is a concern for researchers and educators to conduct research related to students' reversible thinking ability, especially outside the region with topics that are still rarely studied.